Pakistan Economic survey 1979-80 - Government of Pakistan, Finance division Economic adviser's wing, Islamabad (Islamabad : Printing corporation of Pakistan Press Islamabad, 1980)
This Pakistan Economic survey portrays the performance of the national economy with sectoral developments during 1979-80. The analysis focuses on major growth trends and review of selected policy measure taken during the course of the year in the background of the recent past.
Includes bibliographic references.
hza 28/01/2019
Loans
Keywords: Economic growth (Pakistan); Pakistan